Pharmacovigilance during ibrutinib therapy for chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) in routine clinical practice. Issue 6 (3rd June 2017) - Finnes, Heidi D.; Chaffee, Kari G.; Call, Timothy G.; Ding, Wei; Kenderian, Saad S.; Bowen, Deborah A.; Conte, Michael; McCullough, Kristen B.; Merten, Julianna A.; Bartoo, Gabriel T.; Smith, Matthew D.; Leis, Jose; et al.
Abstract: Due to Cytochrome P450 3A (CYP3A) metabolism, clinical trials of ibrutinib-treated chronic lymphocytic leukemia (CLL) patients prohibited concurrent medications metabolized by CYP3A. We evaluated concomitant medication use in 118 ibrutinib-treated CLL patients outside the context of clinical trials. Seventy-five (64%) patients were on medications that could increase ibrutinib toxicity and 4 (3%) were on drugs that could decrease ibrutinib efficacy. Nineteen (16%) patients were on concomitant CYP3A inhibitors (11 moderate, 8 strong), and 4 (3%) were on CYP3A inducers (two patients were on both CYP3A inhibitors and inducers). Although the ibrutinib starting dose was changed in 18 patients on CYP3A interacting medications, no difference in 18-month progression-free survival or rate of ibrutinib discontinuation was observed in patients who were not. In routine clinical practice, 2 of 3 CLL patients commencing ibrutinib are on a concomitant medication with potential to influence ibrutinib metabolism. Formal medication review by a pharmacist should be considered in all patients initiating ibrutinib.